Carborane‐Derived Local Anesthetics are Isomer Dependent. Issue 1 (24th November 2014) - Kracke, George R.; VanGordon, Monika R.; Sevryugina, Yulia V.; Kueffer, Peter J.; Kabytaev, Kuanysh; Jalisatgi, Satish S.; Hawthorne, M. Frederick
Abstract Clinically there is a need for local anesthetics with a greater specificity of action on target cells and longer duration. We have synthesized a series of local anesthetic derivatives we call boronicaines in which the aromatic phenyl ring of lidocaine was replaced with ortho‐, meta‐, C, C'‐dimethyl meta‐ and para‐carborane clusters. The boronicaine derivatives were tested for their analgesic activity and compared with lidocaine using standard procedures in mice following a plantar injection. The compounds differed in their analgesic activity in the following order: ortho‐carborane = C, C'‐dimethyl meta‐carborane > para‐carborane > lidocaine > meta‐carborane derivative. Both ortho‐boronicaine and C, C'‐dimethyl meta‐boronicaine had longer durations of analgesia than lidocaine. Differences in analgesic efficacies are rationalized by variations in chemical structure and protein binding characteristics.